Update on Hyper IgE syndrome (HIES) - Javad Ghaffari; Hamid Ahanchian; Fariborz Zandieh (Mazandaran University of Medical Sciences, 2014)
Hyper IgE Syndrome (HIES) is a rare primary immunodeficiency disease. Most of HIES cases are sporadic. HIES type AD is caused by mutation in signal transducer and activator of transcription-3 (STAT-3). A number of mosaicism HIES has been reported that is associated with intermediate phenotype. Autosomal recessive HIES (AR-HIES) is due to mutation in Dock-8 or cytokine sis 8 and TYK2 or tyrosine kinase 2. The common manifestations are atopic eczema, staphylococcal dermatitis, cellulitis and folliculitis (cold dermal abscesses that are not warm, painful and without redness), recurrent pneumonia and pulmonary abscesses, osteopenia and recurrent bone fracture. The diagnosis of standard HIES is based on clinical suspicion. There is no specific treatment for HIES. The treatment should be based on the prevention of developing infections. Prophylactic antibiotics such as cotrimoxazole and IVIG are administered. Hematopoietic stem cell transplantation was done for all types of HIES, but there is a little information and experience about the long term results of this therapy.